Civil Study Club : Pelatihan Software SAP2000 pada Mahasiswa Teknik Sipil Universitas Teuku Umar - Rahmi, Yulita; Rahman, Aulia; Satria, Andrisman (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
The development of sustainable construction technology requires construction planners to continue to follow technological innovations in the completion of infrastructure projects. One of the basic principles of construction technology that must be carried out is to apply construction technology based on industry 5.0. Therefore, this service aims to provide socialization and training to Teuku Umar University students to be able to use applications that can be used to facilitate the field of construction in the world of technology, namely SAP2000. This service is carried out offline via zoom. The method in this service is that each participant is trained to use the SAP2000 software to master the tools in the software, so that they can model bridges with steel materials, and can produce good designs for construction by providing material, questions and answers, and discussions. The result of this service is the existence of civil study club activities: socialization and training of the SAP2000 software, in the future it is expected to create superior human resources who can master the use of SAP2000 in completing infrastructure construction technology in the world of construction.